Faktor-Faktor yang Berhubungan dengan Tingkat Partisipasi Ibu Balita untuk Menimbang Balita ke Posyandu di Wilayah Kerja Puskesmas Panjang Bandar Lampung Tahun 2010 - Reihana Reihana; Artha Budi Susila Duarsa (Center for Health Policy and Management, 2016)
ABSTRACTBackground: It’s very difficult to find malnourished children in the community because not all mothers are willing to bring their children to integrated service center (Posyandu). Posyandu is one of public facilities in the community to monitor the under five’nutritional status and prevent early nutritional problems. The coverage of under five weighted (D/S) and under five gained weight (N/D) in Bandar Lampung city by 2009 are 79% and 84.90% respectively. Since 2006 until 2009, at Panjang health center, the coverage of D/S show declined trend from 89.2% to 82.6% and still find 2 cases of malnourished children. The pupose of this research is to know the factors associated with the mothers’ participation rate to weigh their under five in Posyandu at Panjang Health Centers by 2010.Methods: This is a quantitative research using cross-sectional study design. The population in this research are all mothers having under five children who live in the area of Panjang Health Centers. The number of sample are 407. The research variables are mothers’ participation to bring their under five to Posyandu, mothers’ age, mother’s education, mother’s occupation, mother’s knowledge, the number of under five in the family, parity, age of under five, husbands’ education, motivation, family support, immunization status, home distance to Posyandu, service provider’s attendance. Data were analyzed by Multiple Logistic Regression prediction model, consisting of univariate, bivariate, and multivariate analysis. Results: The results of this research show that 54.8% mother participate actively to bring their under five in Posyandu. Results of statistical tests reveal that the most dominant factor to encourage mothers’ participation is the interaction among mothers’ knowledge and education OR 4.614 (CI: 3.249-6.551) after controlled variables, mothers’ education OR 0.340 (CI: 0.185-0.625), under five age OR 1.851 (CI: 1.053-3.255),motivation OR 1.037 (CI: 1037-2.780) and family support OR 2.542 (CI: 3.249-4.680).Suggestion: Based on the above research, researcher suggest comprehensive approach to increase Posyandu visit through engaging the team work in Posyandu, promotion and couselling to the mothers who lack of knowledge and education, lack of family support, having under five children and have low motivation. Key words: Integrated Service Center (Posyandu), Participation, Weighing, Under five years. ABSTRAKLatar Belakang: Kasus kurang gizi dan gizi buruk sulit ditemukan di masyarakat karena tidak semua ibu menimbang balitanya ke Posyandu. Posyandu merupakan sarana pelayanan kesehatan di masyarakat untuk memantau keadaan gizi balita dan membantu pencegahan secara dini masalah gizi. Di Kota Bandar Lampung tahun 2009 cakupan D/S dan Cakupan N/D pada balita baru mencapair 79% dan 84,90%. Data cakupan D/S di puskesmas Panjang tahun 2006 – 2009 menunjukkan trend yang menurun dari 89,2% menjadi 82,6% dan masih ditemukan 2 kasus gizi buruk. Tujuan Penelitian diketahuinya faktor-faktor yang berhubungan dengan tingkat partisipasi ibu balita untuk menimbang Balita ke Posyandu di wilayah kerja Puskesmas Panjang tahun 2010.Metodologi: Penelitian ini merupakan penelitian kuantitatif dengan menggunakan desain studi cross sectional. Populasi adalah ibu yang memiliki balita dan tinggal di wilayah kerja Puskesmas Panjang. Besar sampel sebanyak 407. Variabel penelitian adalah partisipasi ibu yang membawa balita ke Posyandu, umur ibu, pendidikan ibu, pekerjaan ibu, pengetahuan ibu, jumlah balita dalam keluarga, paritas, umur anak balita, pendidikan suami, motivasi, dukungan keluarga, status imunisasi, jarak rumah ke Posyandu, kehadiran Petugas. Data dianalisis dengan metode Regresi Logistik Ganda model prediksi, terdiri dari analisis univariat, bivariat, dan multivariate.Hasil: Hasil penelitian mendapatkan 54,8% ibu balita mempunyai partisipasi aktif menimbang balitanya. Hasil uji statistik menunjukkan faktor paling dominan pengaruhnya terhadap partisipasi ibu menimbang balita ke Posyandu adalah interaksi antara pengetahuan ibu dengan pendidikan ibu OR 4,614 (CI : 3,249 – 6,551) setelah dikontrol variabel, Pendidikan ibu OR 0,340 (CI : 0,185 - 0,625), umur balita OR 1,851 (CI : 1,053-3,255), motivasi OR 1,037 (CI : 1.037 - 2,780) dan dukungankeluarga OR 2,542 (CI : 3,249 - 4,680).Saran: Berdasarkan hasil tersebut, Peneliti menyarankan untuk dilakukan pendekatan konfrehensif dalam meningkatkan kunjungan Posyandu, melalui pengaktifan pokjanal, penyuluhan dan konseling pada ibu balita yang memiliki pengetahuan dan pendidikan rendah, tidak ada atau kurang dukungan keluarga, memiliki anak balita dan memiliki motivasi yang rendah. Kata Kunci: Posyandu, Partisipasi, Menimbang, Balita.